Islamic Social Reporting Disclosure Study Of Indonesia And Malaysia Islamic Bank - Anita Dwi Utami (LPPM Universitas Sebelas April, 2022)
Islamic banking is the largest sector in the fast-growing Islamic finance industry. The rapid development of Islamic banking must be accompanied by accountability that is implemented properly, both accountability to fellow humans and accountability to Allah SWT. The COVID-19 pandemic makes a person's survival dependent on others who provide assistance and donations, where this is included in the disclosure of corporate social responsibility as a form of accountability for Islamic banks to fellow humans and Allah SWT. The purpose of this study was to determine the differences in the disclosure of Islamic Social Reporting (ISR) of Islamic banking in Indonesia and Malaysia. The research method used in the study is a comparative quantitative approach. The analytical tool used is the paired sample T-Test. The research sample consists of 54 Islamic banks, 12 Indonesian Islamic banks and 15 Malaysian Islamic banks with 2 years of research, namely 2019 and 2020. The results of the research show that the disclosure of Islamic Social Reporting (ISR) of Indonesian Islamic banking is higher than that of Malaysian Islamic banking and there are differences. There is a significant difference between the disclosure of Islamic Social Reporting (ISR) of Islamic banking in Indonesia and Malaysia.